2009
DOI: 10.1038/ng.430
|View full text |Cite
|
Sign up to set email alerts
|

Loci on 7p12.2, 10q21.2 and 14q11.2 are associated with risk of childhood acute lymphoblastic leukemia

Abstract: To identify risk variants for childhood acute lymphoblastic leukemia (ALL) we conducted a genome-wide association study of 2 case-control series, analyzing the genotypes of 291,423 tagging SNP genotypes in a total of 907 ALL cases and 2,398 controls. We identified risk loci for ALL at 7p12.2 (IKZF1, rs4132601; OR = 1.69, P = 1.20 x 10-19), 10q21.2 (ARIDB5, rs7089424; OR = 1.65, P = 6.69 x 10-19) and 14q11.2 (CEBPE, rs2239633; OR = 1.34, P = 2.88 x 10-7). The 10q21.2 (ARIDB5) risk association appears to be sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
448
3
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 431 publications
(488 citation statements)
references
References 22 publications
(21 reference statements)
32
448
3
5
Order By: Relevance
“…Thus far, GWAS of ALL, including the parent study on which this current analysis is based, have identified four independent loci shown conclusively to be associated with ALL, and more specifically BCP-ALL risk-7p12.2 (IKZF1), 9p12 (CDKN2A/CDKN2B), 10q21.2 (ARID5B) and 14q11.2 (CEBPE). [4][5][6] While the risk of ALL associated with these common variants is not insignificant (RRs of 1.5-1.6), collectively they only underscore B8% of the genetic variance in BCP-ALL risk.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Thus far, GWAS of ALL, including the parent study on which this current analysis is based, have identified four independent loci shown conclusively to be associated with ALL, and more specifically BCP-ALL risk-7p12.2 (IKZF1), 9p12 (CDKN2A/CDKN2B), 10q21.2 (ARID5B) and 14q11.2 (CEBPE). [4][5][6] While the risk of ALL associated with these common variants is not insignificant (RRs of 1.5-1.6), collectively they only underscore B8% of the genetic variance in BCP-ALL risk.…”
Section: Discussionmentioning
confidence: 94%
“…4,6 Briefly, we analyzed 824 pediatric BCP-ALL patients ascertained from the United Kingdom (UK; 464 male, 360 female; mean age at diagnosis 5.4 years, s.d. ¼ 3.6), derived from the United Kingdom Childhood Cancer study 9 (UKCCS), the UK Medical Research Council (MRC) ALL 97 (99) trial and from the Northern Institute of Cancer Research (NICR).…”
Section: Subjects and Methods Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to major chromosomal aberrations, single nucleotide polymorphisms (SNP) were shown to be associated with the development of ALL. For example, SNPs in the genes ARID5B and CEBPE were found to be significantly related to ALL [6]. In addition to structural changes in the genome, epigenetic mechanisms are also important for ALL.…”
Section: Types and Progression Pathways Of Leukemiamentioning
confidence: 99%